Negative pressure wound therapy and conventional wound management at a rural tertiary care center – A comparative study - Dwaipayan Samaddar,; Md. Rijwan Alam,; Jaya Bagchi Samaddar, (Asian Journal of Medical Sciences, 2023)
Background: Wounds are a major source of morbidity and sometimes, mortality and there are several ways to treat them. Negative pressure wound therapy (NPWT) is one way, and this involves the use of a suction device to aspirate and remove fluids, debris, and infectious materials from the wound bed to promote the formation of granulation tissue and wound healing. Another way is with the use of conventional wound dressings. Aims and Objectives: The aim was to compare NPWT and conventional wound dressings for the poor in a rural setting. Materials and Methods: Sixty consecutive cases clinically presenting with wounds between March 2018 and August 2019 were examined and divided into NPWT or conventional wound dressing groups. Outcome was measured by recording wound scores on day 7 or thereafter. Cases and controls were studied from admission until complete healing. Outcome and complications of NPWT and conventional wound dressings were noted. Results were tabulated in MS excel and evaluated using Graphpad Prism 9 software (San Diego, CA, USA). Results: Many patients (33.33%) were in the 5th and 6th decades of life and most (77%) were male. Many wounds were located on the foot (40%). Those patients younger than 40 years of age with a wound <10 days old had a better median wound score in both the groups. The majority of wounds (43.33%) were traumatic. Wound healing was better in non-diabetics and non-smokers. There was a considerable reduction in the organism load in the NPWT group (P=0.0078). Complications were minor. The NPWT group had a significantly shorter mean hospital stay (P=0.0001). Conclusion: NPWT enhanced granulation tissue formation leading to earlier wound healing and faster recovery compared to conventional wound dressings.